2005
DOI: 10.1590/s1413-86702005000100007
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of Western blot/ELISA to improve the serological diagnosis of human tuberculosis

Abstract: Two recombinant antigens and a crude bacterial antigen of a wild M. tuberculosis strain were used to detect specific IgG antibodies in sera from 52 patients with pulmonary tuberculosis, confirmed by an acid-fast smear and serum culture of these patients and that of 25 contacts. The patients were not infected with HIV. We evaluated the sensitivity and specificity of ELISA, based on the recombinant TbF6® ® ® ® ® and TbF6/DPEP antigen and a search for reactivity patterns in the Western blot technique, using whole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Beck et al found at least four serum antibody response profiles when testing human tuberculosis patient sera against M. tuberculosis antigens (2,3). Serum antibody responses are primarily affected by the stage of infection.…”
Section: Vol 13 2006 Characterization Of M Paratuberculosis Proteimentioning
confidence: 99%
“…Beck et al found at least four serum antibody response profiles when testing human tuberculosis patient sera against M. tuberculosis antigens (2,3). Serum antibody responses are primarily affected by the stage of infection.…”
Section: Vol 13 2006 Characterization Of M Paratuberculosis Proteimentioning
confidence: 99%
“…These shortcomings result in the unnecessary treatment of many individuals who may not need it (3,17,32,45). While the tuberculin skin test (TST) and the QuantiFERON-TB Gold (QFT-G), the traditional methods for latent TB infection screening, rely on the cell-mediated response, the humoral response appears to correlate with the progression of the infection to active TB disease (5,6,11,15,20,21).Many studies have been conducted to evaluate the utility of individual specific Mycobacterium tuberculosis antigens for detecting antibodies in patients with active TB disease (1,7,10,11,20,21,25,26,29,38,39,45,46). Several of these antigens have been developed into commercial assays capable of detecting M. tuberculosis antibodies (4,28,35,53).…”
mentioning
confidence: 99%
“…Many studies have been conducted to evaluate the utility of individual specific Mycobacterium tuberculosis antigens for detecting antibodies in patients with active TB disease (1,7,10,11,20,21,25,26,29,38,39,45,46). Several of these antigens have been developed into commercial assays capable of detecting M. tuberculosis antibodies (4,28,35,53).…”
mentioning
confidence: 99%
“…It is further added that H. contortus interaction with host starts after the transition of L 3 into L 4 stage [28]. Furthermore, recombinant protein, having high immunoreactive concentration, may act as best immunodiagnostic antigen by achieving high sensitivity and specificity [29][30][31][32][33][34][35][36]. Recombinant Hc-CS is a major constituent of HcES proteins [23] which may have potential to diagnose H. contortus at early stage of infection.…”
Section: Discussionmentioning
confidence: 99%